Implementing a Filial Group Process to Improve Social Support for Psychological Well-being - Milfayetty, Sri; Rahmulyani, (Advances in Social Sciences Research Journal, 2022)
The study aims to describe the effectiveness of group process filial to improve social support for psychologiacal well-being, A qualitative approach was used in this study with FGD as the data collection method. A total of 25 participants took part in the FGD were designated as Process Group Filial Play (PGFP) participants. These participants were determined based on the PGFP eligibility requirements which are the participans' ability in filial play, as well as the child's psychological well being . The data were analysed using qualitative thematic techniques. The results of data analysis 10 PGFP group process showed an increase in parents’ ability in structuring activity, listening with empathy, playing child-centred imaginary games and setting the boundaries. The results indicated that partipants were able to build a psychologiacal well being . In addition, It has helped children received them selves, good realtionship with other, autonomi, environment involvement, life goal and self growth.